Pioneering Architect in the Construction of Post-Colonial Irak: Rifat Chadirji and His Monument Designs - Melek Kutlu Divleli; Abdullah Asım Divleli (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2023)
The idea of the nation-state, which usually emerges in post-colonial periods, uses architecture as a tool of representation in Iraq, as in many other examples that have experienced similar processes. These architectural designs are not context-free and independent productions but are shaped in parallel with official historiographies. While the official historiography in post-colonial Iraq defines the pre-twentieth century as colonialist, it establishes a relationship of belonging with the ancient Iraqi history and the independence movements of the colonial process. Therefore, the architectural structures produced in this period are shaped in parallel with such a historiographical perspective. Although not all of them are labelled as national, the architectural structures built in post-colonial Iraq have a wide variety. Among them, the monumental monuments and sculptures designed and built by government decisions in the city squares are the most characteristic examples of the nationalization policy. This article focuses on Iraq’s nation-building process during the colonial and post-colonial periods and will tell the story of the construction of two monuments designed by Rifat Chadirji, considered the most influential architect of this period. Since the analysis cannot be done solely through observation, the diaries of the architect during the aforementioned period and before will also be utilized to record his recollections of the design and construction process. This article concludes that the monuments in Iraq are linked to the politics of the period in which they were built. Each has an ideological symbolic value and has played an essential role in shaping national memory.